Ustekinumab dosing, persistence, and discontinuation patterns in patients with moderate-to-severe psoriasis. (April 2015) - Cao, Zhun; Carter, Chureen; Wilson, Kathleen L.; Schenkel, Brad
Abstract Objectives: Ustekinumab is the most recently approved biologic for the treatment of moderate-to-severe psoriasis. Real-world dosing patterns of ustekinumab are yet to be fully characterized. Methods: A retrospective, observational study was conducted using MarketScan Commercial and Medicare databases. A cohort of psoriasis patients treated with ustekinumab between 25 September 2009 and 31 October 2010 was evaluated. Main outcomes included ustekinumab dosing and treatment patterns. Kaplan–Meier estimates were calculated to adjust for the censoring of data. Subgroup analysis was conducted for biologic-experienced patients and biologic-naïve patients. Results: One thousand ustekinumab patients were included, of whom 60% were biologic-experienced. The average age was 49.0 and 53.9% were male. 63.3% of patients initiated ustekinumab with a 45 mg dose and 34.5% initiated with a 90 mg dose. Mean (median) days from initial dose to second dose was 31.1 (28.0). During maintenance therapy, dose intervals spanned from 80.6 to 81.2 (84.0) days. About 81.4% of patients were persistent during the variable-length follow-up period. Conclusions: The majority of patients received the 45 mg ustekinumab dose. The mean dosing intervals were consistent with the US prescribing guidelines. Biologic-naïve and biologic-experienced patients had similar dosing patterns. Ustekinumab treatment achieved a persistency rate as high as 81.4% over an average of 186.5 (SD 114.2) days of follow-up.